Understanding ‘God as Reality’: Analysis of the Ontological Approach in the Tradition of Islamic Philosophy and Sufism - Arroisi, Jarman; Zarkasyi, Hamid Fahmy; Salim, Mohammad Syam’un; Taqiyuddin, Muhammad (Journal of Islamic Thought and Civilization, 2022)
In contrast to the West, which considers God as a myth and negates values ​​about reality and truth, the Muslim philosophers and Sufis base their knowledge on the concept of God that has been established in Islam. This article describes the approach of the Sufis and the Muslim philosophers regarding God as reality and truth. By using the descriptive analysis method, this study draws conclusions based on various arguments: first, there is a meeting point between the two, especially in terms of ’al-Haqq’ as one of the ’Names’ (asmā) of Allah which also means ’reality’ and ’truth’ which are linguistically unified. Therefore, everything that is called ’reality’ has to do with the existence of God which provides wisdom behind all reality as God’s creation. Because God created reality with a ’true’ purpose. Second, despite the fundamental differences in various worldviews, the West has never assumed that God is Reality in itself because its worldview has negated the Diversity of metaphysical reality. This is also affirmed, only at the metaphysical level as ’speculative science’ or ’noumena’ in Kant’s account. Third, different from the West in Islam, there are various treasures of intellectual property discussions about God as Reality. Although there are many schools in understanding God as Reality, the Muslims have almost the same opinion because they affirm revelation as the only authoritative source of explanation for the concept of God. Keywords: Reality, Truth, Muslim philosophers, Sufism, al-Haqq, Worldview, Epistemology